Taking an Army from Dictatorship to Democracy: Lessons Learned by the Bundeswehr in Absorbing the East German Army - Corum, James Sterling (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2014)
After the reunification of Germany, the Bundeswehr had to take over the former East-German army (Nationale Volksarmee, NVA). The reduction in the numbers of military staff throughout Eastern Europe after the Cold War also made the task more difficult. Researchers from the Bundeswehr Institute of Social Sciences interviewed East-German soldiers immediately after reunification. They found that most of them were obedient followers whose professional skills were good, but who had no initiative. The strong influence of dogmatic communist ideology was also a problem. Many former East-German officers thought that West Germany also had one book of truth that taught them the new, correct understanding of history, politics and society.The East-German army was not popular among the population. The status of an officer in society was privileged and there were many of them – similar to the Soviet army, junior officers in the East-German army served in positions that in western armies are covered by non-commissioned officers. Conscripts were almost fully at the mercy of the officers.There were ca 42,000 officers in the NVA at the end of 1989. More than 99%of East-German officers were members of the Socialist Union Party of Germany. Approximately 10,000 political officers served in the NVA. Approximately 50,000 active servicemen, incl. 23,000 officers, were to be transferred according to the takeover plan.These servicemen were put on probation for two years, and once it was completed the 28-member Independent Committee selected those who wereto be offered the opportunity to join the Bundeswehr career system. All political officers were the first to be let go, but generals, colonels (with acouple of exceptions) and all officers over 55 years ago were also released from duty. As for the remaining officers, everyone who was known to have cooperated with the secret services of East Germany was immediately fired. 30,000 of the 50,000 officers and non-commissioned officers transferred by the Bundeswehr soon resigned.